STRATEGY OF ACCELERATE THE APPLICATION BIODIESEL IN KRI KOARMADA II TO INCREASE ALUTSISTA COMBAT READINESS - Heru Prasetia; Okol Sri Suharyo; Udisubakti Cipto Mulyono (Indonesian Naval Technology College STTAL, 2021)
Through.Presidential.Regulation No. 5 of 2006 on National.energy.policy.and Esdm.Ministerial Regulation No.32 of 2008, the Government.encourages.the use of biodiesel in all aspects. In KRI, the use of biodiesel is only for KRI with machines that are still conventional or have not used a common rail system. Until 2020 KRI that has migrated to biodiesel is 32.5% of 40 KRI. Switching to biodiesel is not an easy matter, this is due to the complexity of the problems in KRI, both in terms of the limited budget, material components that do not support biodiesel, maintenance, and operations. Therefore, the writing of this journal aims to.formulate a strategy to.accelerate the application of biodiesel in KRI in Koarmada II by using the TOWS method (Threats, Opportunities, Weakness, Strength). The results of the analysis based on TOWS analysis obtained quadrant strategy is in quadrant III which is a Turn-around strategy that means making a strategy by suppressing weaknesses by utilizing existing opportunities. The development of the strategy resulted in 7 relevant sub-strategies to be used as an effort to accelerate the application of biodiesel to KRI in the Koarmada II. Keywords: Renewable energy, Biodiesel, KRI, TOWS.